(untitled) - McBride, Dawn M. (Thousand Oaks, CA, 2016)
Using diverse examples from published research, the Third Edition of The Process of Research in Psychology by Dawn M. McBride provides step-by-step coverage on how to design, conduct, and present a research study. Early chapters introduce important concepts for developing research ideas while subsequent "nuts and bolts" chapters provide more detailed coverage of topics and examine the types of research relevant to the field. This logical two-part structure creates an excellent foundation upon which students can build their knowledge of the entire research process.
Keywords: Tâm lý học,Psychology,Tâm lý học, thí nghiệm,Psychology, Experimental; Nghiên cứu,Phương pháp luận,Research,Methodology